#TITLE_ALTERNATIVE# - RELIGIA (NIM : 10311001), BAHAR
Indonesia is an area that is pretty much traversed by the equator. In addition, Indonesia has coverage southern skies and the northern sky fairly extensive. This makes Indonesia as a country that has the potential to contribute astronomical data for the southern skies and the northern sky. This is what makes the motivation of authors to conduct a sky survey. Needs sky survey is needed in this world. In addition to the data mining needs of the heavens, but also for the safety of Earth itself from the threat of space object. In a large project in the world, many of which have already started to survey the sky, particularly in the Solar System survey of small objects such as asteroids, comets, satellites, and spacecraft Earth. This is due to the lack of data for small solar system objects. In this study, there is one institution that is Spaceguard under IAU to deal with the dangers of space for our Earth and provide alerts if there are celestial bodies will approach the Earth. In addition, the Minor Planet Center (MPC) under the auspices of the IAU also provide and accept data from all the observatory for small objects of this solar system. Of the existing needs, the survey system to be automated, because there may be an observatory can provide continuous data if still using manual systems. The higher the need for data and the absence of adequate systems in Indonesia to conduct a survey, therefore, there needs to be a system that supports survey, both in hardware and software. Of necessity this survey, the author makes an automated system to conduct surveys, and make software for system control and data processing to detect moving objects automatically.